The Impact of Macroeconomic Indicator on Islamic Insurance Demand in Indonesia - Ayyubi, Salahuddin El; Widyastutik, W; Anditta, A. (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2019)
This research aimed to determine the development of the Islamic insurance industry in Indonesia and analyze the influence of macroeconomic indicators on Islamic insurance demand in Indonesia. Ordinary Least Square (OLS) was used in this research with monthly time series data from January 2014 to December 2016. The results of this research indicated that the variables of money supply, interest rate, GDP per capita, and education had a positive (significant) effect on the Islamic insurance demand in Indonesia. Moreover, the inflation variable and dependency ratio had a negative (significant) effect on the Islamic insurance demand in Indonesia.Abstrak:Penelitian ini bertujuan untuk melihat perkembangan industri asuransi Islam di Indonesia dan menganalisis pengaruh indikator makroekonomi terhadap permintaan akan asuransi Islam. Penelitian ini menggunakan Ordinary Least Square (OLS) dengan rangkaian data bulanan dari Januari 2014 hingga Desember 2016. Penelitian menunjukkan bahwa variabel penawaran uang, tingkat suku bunga, PDB per kapita, dan pendidikan berdampak positif (signifikan) terhadap permintaan akan asuransi Islam di Indonesia. Selain itu, variabel inflasi dan rasio ketergantungan berdampak negatif (signifikan) terhadap permintaan tersebut.